Effect of carbohydrate intake on half-marathon performance of well-trained runners - Burke, L. M.; Wood, C.; Pyne, D. B.; Telford, R. D.; Saunders, P. U. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
Eighteen highly-trained runners ran two half marathons in mild environmental conditions, 3 wk apart, consuming either 426 ± 227 mL of a flavored placebo drink (PLACEBO) or an equivalent volume of water (386 ± 185 mL) and a commercial gel (GEL) supplying 1.1 ± 0.2 g/kg body mass (BM) carbohydrate (CHO). Voluntary consumption of this fluid was associated with a mean BM change of ~ 2.4%. Runners performed better in their second race by 0.9% or 40 s (P = 0.03). Three runners complained of gastrointestinal discomfort in GEL trial, which produced a clear impairment of half-marathon performance by 2.4% or 105 s (P = 0.03). The effect of GEL on performance was trivial: time was improved by 0.3% or 14 s compared with PLACEBO (P = 0.52). Consuming the gel was associated with a 2.4% slower time through the 2 x 200 m feed zone; adding a trivial ~ 2 s to race time. Although benefits to half marathon performance were not detected, the theoretical improvement during 1-h exercise with CHO intake merits further investigation.